KORELASI KEMANDIRIAN BELAJAR DENGAN HASIL BELAJAR SISWA KELAS IV SEKOLAH DASAR - Topan Ponira; Siti Halidjah; Rio Pranata (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe purpose of this article was to describe correlation between learning independenceand student learning outcomes in thematic learning of grade IV SDN 16 PontianakEast. Method used is a descriptive method with a form of correlation study research.Population in this study is all students of grade IV SDN 16 Pontianak East. Samplingusing purposive sampling technique with a sample number of 30 people of grade IVASDN 16 Pontianak East. Data collection techniques are indirect communicationtechniques and documentary study techniques. Communication techniques are notdirectly used to collect data on the independence of learning results with tools in theform of questionnaires while documentary study techniques are used to collect data onstudents' learning outcomes. Analysis of data conducted with statistical analysisshowed that student learning independence averaged 84,4, student learning outcomesaveraged 87,07, and correlation between student self-reliance and student learningoutcomes of rhitung=0,301 with rtabel=0,361 sign age 5%. Based on the data, it isconcluded that there is no correlation between learning independence and studentlearning results in thematic learning class IV SDN 16 pontianak East.Keywords: Correlation, Learning Independence, Learning Outcomes.